Solve the following system of equations, using the graphing method:
x + 2y = 4
2x - y = 3

The solutions for the systems x + 2y = 4, 2x - y = 3 are x = 2, y = 1. Multiply x + 2y = 4 by -2: -2x - 4y = -8; (-2x - 4y = -8) + (2x - y = 3): -5y = -5; y = 1; Solve for x: x + 2(1) = 4; x + 2 = 4; x = 4 - 2; x = 2

Question

Asked 4/27/2013 6:02:17 AM

Updated 10/1/2014 6:22:14 AM

1 Answer/Comment

Edited by jeifunk [10/1/2014 6:04:30 AM]

Rating

3

The solutions for the systems x + 2y = 4, 2x - y = 3 are x = 2, y = 1.

Multiply x + 2y = 4 by -2:

-2x - 4y = -8;

(-2x - 4y = -8) + (2x - y = 3):

-5y = -5;

y = 1;

Solve for x:

x + 2(1) = 4;

x + 2 = 4;

x = 4 - 2;

x = 2

Multiply x + 2y = 4 by -2:

-2x - 4y = -8;

(-2x - 4y = -8) + (2x - y = 3):

-5y = -5;

y = 1;

Solve for x:

x + 2(1) = 4;

x + 2 = 4;

x = 4 - 2;

x = 2

Added 10/1/2014 6:22:14 AM

This answer has been confirmed as correct and helpful.

Solve this proportion: x + 1 over 6 and x + 2 over 4. Here are the multiple choices: { - 4} {3} {1/2} { - 6}
User: That is incorrect, please look at the multiple choices. **Weegy:** How to Construct Better
Multiple-Choice Tests
This section is intended for school, college, [ [ and university teachers.
When to use multiple-choice: advantages and disadvantages
How to write a good multiple-choice question
Advanced techniques for innovative multiple-choice questions
Advanced techniques for testing higher level thinking
Question Arrangement on Tests.
Multiple-Choice Construction Checklist
Frequently Asked Questions about Multiple-choice
Multiple-Choice Glossary
References: Useful textbooks and relevant websites
] ] (More)

Question

Expert Answered

Updated 8/6/2014 9:35:18 PM

1 Answer/Comment

-4 is the answer for x + 1 over 6 and x + 2 over 4.

(x+1)/6=(x+2)/4

(x+1)/3=(x+2)/2

2*(x+1)/3=x+2

2x+2=3(x+2)

2x+2=3x+6

3x-2x=2-6

x=-4.

(x+1)/6=(x+2)/4

(x+1)/3=(x+2)/2

2*(x+1)/3=x+2

2x+2=3(x+2)

2x+2=3x+6

3x-2x=2-6

x=-4.

Added 8/6/2014 9:27:22 PM

This answer has been confirmed as correct and helpful.

Solve this proportion: x + 1 over 6 and x + 2 over 4. Here are the multiple choices: { - 4} {3} {1/2} { - 6}
**Weegy:** The proportion for the equation x+1/6, x+1/2 is (1/6+x)+(1/2+x) = 2 x+2/3. (More)

Question

Expert Answered

Updated 8/6/2014 9:35:00 PM

1 Answer/Comment

-4 is the answer for x + 1 over 6 and x + 2 over 4.

(x+1)/6=(x+2)/4

(x+1)/3=(x+2)/2

2*(x+1)/3=x+2

2x+2=3(x+2)

2x+2=3x+6

3x-2x=2-6

x=-4.

(x+1)/6=(x+2)/4

(x+1)/3=(x+2)/2

2*(x+1)/3=x+2

2x+2=3(x+2)

2x+2=3x+6

3x-2x=2-6

x=-4.

Added 8/6/2014 9:28:51 PM

This answer has been confirmed as correct and helpful.

Solve the linear equation.
-2x - 2 + 7(x + 1) = 2x - 4 **Weegy:**
-2x - 2 + 7(x + 1) = 2x - 4;
-2x - 2 + 7x + 7 = 2x - 4;
5x + 5 = 2x - 4;
5x - 2x = -4 - 5;
3x = -9;
x = -9/3;
x = -3
**User:** Solve and check the linear equation.
6x - 7 + 3(x + 1) = 4x - 6 (More)

Question

Expert Answered

Updated 8/5/2014 10:56:52 PM

1 Answer/Comment

6x - 7 + 3(x + 1) = 4x - 6;

6x - 7 + 3x + 3 = 4x - 6;

9x - 4 = 4x - 6;

9x - 4x = -6 + 4;

5x = -2;

x = -2/5

6x - 7 + 3x + 3 = 4x - 6;

9x - 4 = 4x - 6;

9x - 4x = -6 + 4;

5x = -2;

x = -2/5

Added 8/5/2014 10:56:52 PM

This answer has been confirmed as correct and helpful.

Solve the following system of equations: x + 2y = 4 2x - y = 3 Here are the multiple choices: (2, 1) (-1, -3) (0, 4) (5, -2)

Question

Not Answered

Updated 3/1/2015 2:59:43 AM

1 Answer/Comment

The solution set for the systems x + 2y = 4, 2x - y = 3 is: (2, 1)

(x + 2y = 4) * (-2);

-2x - 4y = -8;

(-2x - 4y = -8) + (2x - y = 3);

-5y = -5;

y = 1;

x + 2 = 4;

x = 4 - 2;

x = 2

(x + 2y = 4) * (-2);

-2x - 4y = -8;

(-2x - 4y = -8) + (2x - y = 3);

-5y = -5;

y = 1;

x + 2 = 4;

x = 4 - 2;

x = 2

Added 3/1/2015 2:59:43 AM

This answer has been confirmed as correct and helpful.

Solve the following system of equations, using the elimination method: 5x + 3y = -7 7x - 3y = 55
**Weegy:** Solve the following system of equations, [ using the elimination method: 5x + 3y = -7 7x - 3y = 55
Answer 5x + y = -17 - - - > 15x + 3y = -51 {multiplied top equation by 3}
7x - 3y = -37
15x + 3y = -51 {new top equation}
7x - 3y = -37 {original bottom equation}
- - - - - - -
22x = -88 {added the two equations together}
x = -4 {divided both sides by 22}
5x + y = -17 {top equation}
5(-4) + y = -17 {substituted -4, in for x, into top equation}
-20 + y = -17 {multiplied 5 by -4}
y = 3 {added 20 to both sides}
x = -4 and y = 3
Source ] **User:** Here are the multiple choices: (4, -9)
(3, -6)
(0, -14)
(7, 3) (More)

Question

Expert Answered

Updated 6/23/2014 10:41:41 PM

1 Answer/Comment

5x + 3y = -7

7x - 3y = 55

adding up equations the result is:

12x = 48

x = 48/12 = 4

5(4) + 3y = -7

20 + 3y = -7

3y = -7 - 20 = -27

y = -27/3 = -9

The solution for the system 5x + 3y = -7 7x - 3y = 55 is (4, -9)

7x - 3y = 55

adding up equations the result is:

12x = 48

x = 48/12 = 4

5(4) + 3y = -7

20 + 3y = -7

3y = -7 - 20 = -27

y = -27/3 = -9

The solution for the system 5x + 3y = -7 7x - 3y = 55 is (4, -9)

Added 6/23/2014 10:41:41 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/23/2014 11:34:32 PM]

27,674,390

questions answered

There are no comments.